The Effectiveness of Using Guided Reading Strategy to Improve Students’ Reading Comprehension - Widia Audira; Sofyan A. Gani; Diana Fauzia Sari (Universitas Syiah Kuala, 2020)
This research belongs to experimental quantitative research and was carried out at SMPN 16 Banda Aceh. The sample was eight grade students which consists of 30 students. In collecting the data, the researcher used pre-test, treatment and post-test with 27 multiple choices as scoring. Then data was analysed using t-test formula. The researcher used recount text as the topic of the reading passage when the students were given pre-test, treatment, and post-test. The aim of this research was to investigate whether or not guided reading strategy can improve students’ score in reading comprehension at SMPN 16 Banda Aceh. Therefore, the result had positively answered the research question stated in the beginning of the study. The result showed students’ mean of pre-test was 32, while the mean of post-test was 78. The hypothesis result by using t-test showed that the obtained t-score was higher than t-table (8.17 2.052) , the difference is statistically significant. Therefore, based on the complication, there is significant difference in reading comprehension score of students before given treatment using guided reading strategy and after treatment. Thus, it can be said that guided reading strategy improved students’ reading comprehension and hence Ha is accepted because after given treatment by guided reading strategy, the students had better achievement in reading comprehension.